Another woman - Vincenzi, Penny (New York orion, 1995)
When the seemingly elated Cressida Forrest disappears without a trace the night before her lavish wedding, a frantic search for answers reveals a fragile web of sexual and financial secrets involving two families
1
Keywords: Family secrets -- Fiction; Missing persons -- Fiction; Runaway wives -- Fiction; Domestic fiction